CORPORATE SOCIAL RESPONSIBILITY DAN UPAYA PEMENUHAN HUMAN SECURITY MASYARAKAT (STUDI KASUS KEGAGALAN PENGIMPLEMENTASIAN CSR OLEH PT. SEMEN TONASA) - , Dian Ekawaty ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Thesis entitled âCorporate Social Responsibility and an effort to complience human security of the society ( case study the failure on the CSR implementation of PT. Semen Tonasa)â aims to shed light on the causes of the failure of the company improve the condition of human security Biring Ere Villagers through CSR programs. This thesis raises the issue of the implementation of CSR related causes of failure of PT. Semen Tonasa. To answer the research questions posed to use the concept of CSR, Community participation, and human security. Qualitative methods chosen so that the problem can be analyzed in more depth. The data used are secondary data and primary data, where the primary data is obtained by conducting interviews with several informants involved in the implementation of CSR. This study does not cover the implementation of CSR as a whole but done periodicity, that is the implementation of CSR in 2011 and 2012. Based on information obtained in the field it appears that PT. Semen Tonasa has implemented CSR regularly every year with great financial support, even PT. Semen Tonasa has had a special department that handles the company's CSR program. The evidence suggests CSR program PT. Semen Tonasa implemented under the Ministry of CSR and Public have not been able to bring an improvement in the conditions of human security that focuses in this study is the economic, health, and environment Biring Ere Villagers. Condition is happening is an increase in the number of poor families that do not show the environmental conditions that affect the rate of improvement of health of citizens. The failure PT. Semen Tonasa in implementing CSR programs resulting from the implementation of CSR motives are still based on legal considerations to avoid the company of legal sanctions. In addition to related motives, failures also is the impact of the lack of community involvement in every stage of CSR implementation.